Bond market spillover networks during the global pandemic: What we learned from ASEAN-4 markets - Mohammed Gazi Salah Uddin; Muhammad Yahya; Donghyun Park; Axel Hedström; Shu Tian (Asian Development Bank Institute (ADBI), 2023)
During decades of market development, the individual financial markets of the member economies of the Association of Southeast Asian Nations (ASEAN) have been progressively incorporated into regional and international markets. The aim of this study is to explore and measure the strength and direction of the bond market connectedness between Indonesia, Malaysia, the Philippines, and Thailand-collectively known as ASEAN-4-and major global and regional bond markets and to identify various factors affecting spillover effects. This study derives a risk spillover measure based on the attributes of static and dynamic spillover models and empirically examines its role in receiving or transmitting shocks based on different information spillover or contagion channels. In particular, the objective of this study is to evaluate the connectedness dynamics empirically using government bond yields in ASEAN-4 markets, major regional markets (the People's Republic of China, Japan, and the Republic of Korea), and major global markets (the European Union, the United Kingdom, and the United States). We aim to examine risk spillovers in ASEAN-4 bond markets and identify the potential economic and financial fundamentals driving uncertainty spillovers. We find complex intra-group return and volatility connectedness among ASEAN-4 markets and moderate inter-group return and volatility connectedness between ASEAN-4 and regional and global markets at different time horizons.
Keywords: F21; G12; G15; J11; M48; N25; O11; 330; ASEAN-4 bond markets; COVID-19; spillover; uncertainty; volatility